PENGARUH STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. SEMBILAN PILAR UTAMA KABUPATEN KEPAHIANG - Islamuddin Islamuddin; Yosen Jayo (Yayasan Insani Mandiri Santani, 2023)
This study aims 1) to determine the effect of work stress on the performance of employees of PT. The Nine Main Pillars of Kepahiang Regency. 2) To determine the effect of job satisfaction on the performance of employees of PT. The Nine Main Pillars of Kepahiang Regency. 3) To find out the effect of job stress and job satisfaction on the performance of employees of PT. The Nine Main Pillars of Kepahiang Regency. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all employees of PT. The Nine Main Pillars of Kepahiang Regency consist of 50 employees. the sample is 50 employees of PT. The Nine Main Pillars of Kepahiang Regency.Based on the results of research on the effect of job stress and job satisfaction on employee performance at PT. Nine Main Pillars of Kepahiang Regency, the following conclusions can be drawn: 1) There is a negative and significant effect of work stress (X1) on employee performance (Y) PT. Nine Main Pillars of Kepahiang Bengkulu Regency. 2) There is a positive effect of job satisfaction (X2) on employee performance (Y PT. Sembilan Pilar Utama Kepahiang Regency, Bengkulu Regency. 3) Job stress and job satisfaction together affect the performance of PT. Nine Main Pillars of Kepahiang Regency, Bengkulu Regency. Keywords: Job Stress, Job Satisfaction, Employee Performance,